ответ: 1) x = (a + b) / (a - b); a ≠ b; 2) x = 2 · (m - n); 3) x = a + 1;
4) x = (3 · (m - n)) / (m + n); m ≠ - n
Объяснение:
1) a²x - b²x = a² + 2ab + b²; x · (a - b) · (a + b) = (a + b)²; x = (a + b)² / (a - b) · (a + b)
x = (a + b) / (a - b); a ≠ b
2) 3mx + 3nx = 6m² - 6n²; 3 · x · (m + n) = 6 · (m + n) · (m - n);
x = (6 · (m + n) · (m - n)) / 3 · (m + n); x = 2 · (m - n)
3) ax + x = a² + 2a + 1; x · (a + 1) = (a + 1)²; x = (a + 1)² / (a + 1) = a + 1; x = a + 1
4) m²x + 2mnx + n²x = 3m² - 3n²; x · (m + n)² = 3 · (m + n) · (m - n);
x = (3 · (m + n) · (m - n)) / (m + n)²; x = (3 · (m - n)) / (m + n); m ≠ - n
(x-a) (x + y)=х²+ху-ах-ау
(t + s)(b + k)=tb+tk+sb+sk
(a + 2) (6-3)=3(a+2)=3a+6
(d - 4) (t + 5)=dt+5d-4t-20
(a + 2)(n - m)=an-am+2n-2m
(c - d) (x - y)=cx-cy-dx+dy
(4-6) (5 + c)=-2(5+c)=10+2c
(k-6) (7-d)=7k-dk-42+6d